Dual Output Five-Level Converter with Reduced Switch Count - Kumar P.; Dwivedi D.; Chinmaya K.A. (My University, 2025)
This work presents a novel dual output five-level voltage (FL- DOV) converter topology designed to supply two independent loads simultaneously. The proposed FL-DOV converter significantly reduces the number of switches required compared to traditional five-level multilevel inverters (MLIs) when driving two loads. This reduction in switch count leads to decreased complexity and potential cost savings. A level-shifted in-phase disposition pulse width modulation (PWM) technique is utilized to achieve efficient switching and improved performance. Extensive simulation studies conducted in the MATLAB/Simulink environment demonstrate the effectiveness and feasibility of the proposed converter. The results validate the FL-DOV converter's capability to deliver efficient and reliable power to two loads concurrently. This research advances the dual-output inverters by presenting a more efficient and streamlined solution for powering two loads, contributing to the development of versatile and cost-effective power electronic systems. © 2024 IEEE.